A Navigation and Control System for a Mobile Robot for Patrolling Buildings - Robert GŁĘBOCKI; Paweł KICMAN; Antoni KOPYT (Problemy Mechatroniki)
This paper presents the work completed under a research project titled "Design of a mobile platform for the support of forensic testing of scenes with potential CBRN hazards". The study focuses on operation of the mobile platform control algorithm, determination of the mobile platform position and preparation of the mobile platform system for integration with a video navigation system. The sensors installed on the mobile platform are intended as emergency backup systems in the event of loss of communication between the platform and its operator. The results of the test drive sessions completed to verify the control algorithm performance are also given.